2009
DOI: 10.1177/030802260907200307
|View full text |Cite
|
Sign up to set email alerts
|

Graduates' Reflections on their Preparation for Practice

Abstract: New graduates are the life blood of the occupational therapy profession. It is important that they are equipped to practise in the current health care environment and are confident about their professional contribution. This New Zealand study explored new graduates' perceptions of how well they had been prepared for practice, using three focus groups of graduates from one occupational therapy programme. The findings confirmed that the biggest issues for new graduates were searching for role clarity, inadequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 26 publications
3
65
0
1
Order By: Relevance
“…To allow participants to qualify their answers to closed-ended questions, space was made for additional comments. Descriptors for the section on general CS experience were extracted from published articles on novice practitioners' experiences of practice [46][47][48][49][50][51][52][53][54] . Descriptors were grouped into four areas of professional practice: knowledge and skill in practice (13 items), professional identity and recognition (8 items), supervision and support (7 items), and positive and negative personal descriptors (20 items).…”
Section: Instrumentationmentioning
confidence: 99%
“…To allow participants to qualify their answers to closed-ended questions, space was made for additional comments. Descriptors for the section on general CS experience were extracted from published articles on novice practitioners' experiences of practice [46][47][48][49][50][51][52][53][54] . Descriptors were grouped into four areas of professional practice: knowledge and skill in practice (13 items), professional identity and recognition (8 items), supervision and support (7 items), and positive and negative personal descriptors (20 items).…”
Section: Instrumentationmentioning
confidence: 99%
“…The importance of supervision from an experienced therapist in the same profession should not be underestimated; supervision is important in assisting new graduates as they build confidence and profession specific skills, and very importantly, for the development of professional identity [5]. A study of one hundred and fifty-one New Zealand and Australian occupational therapy graduates found that 96% of new graduates who received supervision reported that it facilitated their development of clinical skills, enhanced the quality of service to clients, and clarified their role as an occupational therapist.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been frequently reported that new graduates often expect supervisors to provide specific and regular support but are often dissatisfied with the amount of supervision provided [15]. Studies show that graduates reported wanting more support, in the form of preceptorship and supervision, than was readily available [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, issues such as perception and attitudes of new graduates, supervision arrangements and factors influencing choice of employment have the focus of research (Adamson, Hunt, Harris & Hummel, 1998;Gray et al, 2012;Hummell & Koelmeyer, 1999;Rugg, 1996). Studies that have considered new graduates preparedness for practice highlight a particular area of weakness in relation to a perceived lack of technical intervention and practical skills (Hodgetts et al, 2007;Robertson & Griffiths, 2009). Although an earlier study by Atkinson and Steward (1997) revealed that new graduates felt well prepared in selfmanagement and their ongoing professional development.…”
Section: Introductionmentioning
confidence: 99%